2017
DOI: 10.1016/j.bjm.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic comparison and mortality of Beauveria bassiana against cabbage caterpillar Pieris brassicae LINN

Abstract: Beauveria bassiana, an entomopathogenic fungus, is the alternative biocontrol agent exploited against major economic crop pests. Pieris brassicae L. is an emerging pest of the Brassicaceae family. Therefore, in the present study, fungal isolates of Beauveria bassiana, viz. MTCC 2028, MTCC 4495, MTCC 6291, and NBAII-11, were evaluated for their virulence against third instar larvae of P. brassicae. Among all these fungal isolates, maximum mortality (86.66%) was recorded in B. bassiana MTCC 4495 at higher concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 36 publications
3
40
2
3
Order By: Relevance
“…Proteolytic activity of the three EPF isolates was similar to that reported by Petlamul and Prasertsa (2012). Different assays were performed to detect protease production by EPFs in cultures (Ali et al 2011: Dhawan andJoshi 2017). The high level of protease activity was detected in the culture filtrate of M. anisopliae (Petrisor and Stoian 2017) and B. bassiana (Donatti et al 2008).…”
Section: Proteolytic Activity Of Epf Isolatessupporting
confidence: 70%
See 2 more Smart Citations
“…Proteolytic activity of the three EPF isolates was similar to that reported by Petlamul and Prasertsa (2012). Different assays were performed to detect protease production by EPFs in cultures (Ali et al 2011: Dhawan andJoshi 2017). The high level of protease activity was detected in the culture filtrate of M. anisopliae (Petrisor and Stoian 2017) and B. bassiana (Donatti et al 2008).…”
Section: Proteolytic Activity Of Epf Isolatessupporting
confidence: 70%
“…They found that the optimum incubation period for protease activity was 4-6 days. Recently, Dhawan and Joshi (2017) recorded the maximum protease activity of B. bassiana to be 6-8 days of incubation.…”
Section: Effect Of Limiting Factors On the Proteolytic Activity Of Epmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that the protein content was much higher on day 1 than in subsequent days in both B. bassiana-infected and non-infected caterpillars as the larvae has just molted into 3rd-instar (Table S2). Dhawan and Joshi (2017) was higher at the fifth day compared with the other days 3-4 after treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have documented that the infection of this pathogen can induce humoral immune responses in caterpillars and result in an increase in lysozyme activity in the hemolymph (Boucias, Hung, Mazet, & Azbell, 1994;Wojda, Kowalski, & Jakubowicz, 2009). Meanwhile, others have reported that such infection has led to an irregular change of the protein (Wang, Lv, Xie, & He, 2010) and a variation in lipid content (Dhawan & Joshi, 2017) in caterpillars. However, how plants affect these indicators linked to disease resistance against the infection of B. bassiana, has not been explored.…”
Section: Knowledge Of the Relationships Among Plants Insect Herbivoresmentioning
confidence: 99%